Respuesta :
Answer:
y = -3
Step-by-step explanation:
(3,-3)
m = 0
Slope-intercept:
y - y1 = m(x - x1)
y + 3 = 0(x - 3)
y + 3 = 0
y = -3
Answer:
y=-3
Step-by-step explanation:
slope-intercept form of the line is given as y=mx+b, where m is the slope and b is the y intercept.
we know the slope (m) and the point (3,-3)
substitute what is known into the equation:
y=0x+b
or:
y=b
since the point will pass through the point (3,-3), we can substitute the values of the point into the equation to find b
-3=0(3)+b
-3=b
therefore the equation is y=-3
hope this helps!